Effects of non-Newtonian lubricants and elastic coating on transient elastohydrodynamic lubrication at impact squeeze loading. (July 2019) - Chu, Li-Ming; Chang, Yuh-Ping; Hsu, Hsiang-Chen
This study explores the effects of non-Newtonian lubricants on elastohydrodynamic lubrication with coating at impact and rebound loading using power law lubricants. The coupled transient modified Reynolds, rheology, elasticity deformation, and ball motion equations are solved simultaneously, thus obtaining the transient pressure profiles, film shapes, normal squeeze velocities and accelerations. The effect of the flow index ( n ) is equivalent to enhancing the lubricant viscosity, also enlarging the damper effect. The simulation results reveal that the film thickness, the primary peak, and the secondary peak increase with increasing the flow index. The greater the flow index is, the earlier the dimple form, and the smaller the maximum value of the impact force is. The rebounding velocity and the peak value of acceleration increase with decreasing the flow index. Moreover, this research possesses academic innovation and industrial application.